2009
DOI: 10.1038/nn.2313
|View full text |Cite
|
Sign up to set email alerts
|

Na+-activated K+ channels express a large delayed outward current in neurons during normal physiology

Abstract: One of the largest components of the delayed outward current active during normal physiology in many mammalian neurons such as medium spiny neurons of the striatum and tufted–mitral cells of the olfactory bulb, has gone unnoticed and is due to a Na+-activated-K+-current. Previous studies of K+ currents in mammalian neurons may have overlooked this large outward component because the sodium channel blocker tetrodotoxin (TTX) is typically used in such studies; we find that TTX also eliminates this delayed outwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
114
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 27 publications
12
114
0
Order By: Relevance
“…1 B), and when external Na ϩ was substituted with NMG, I K of DRG neurons was greatly reduced, to ϳ40% its control value (n ϭ 6). This is very similar to K Na reported in Xenopus spinal neurons (Dale, 1993), lamprey spinal cord neurons (Hess et al, 2007), and rat olfactory neurons (Budelli et al, 2009). These cultured embryonic neurons are ideal because they are also homogenous in their firing properties (Chen et al, 1987;Grigaliunas et al, 2002;Toman et al, 2004).…”
Section: Cultured Drg Neurons Contain Slack K Na Channelssupporting
confidence: 87%
See 2 more Smart Citations
“…1 B), and when external Na ϩ was substituted with NMG, I K of DRG neurons was greatly reduced, to ϳ40% its control value (n ϭ 6). This is very similar to K Na reported in Xenopus spinal neurons (Dale, 1993), lamprey spinal cord neurons (Hess et al, 2007), and rat olfactory neurons (Budelli et al, 2009). These cultured embryonic neurons are ideal because they are also homogenous in their firing properties (Chen et al, 1987;Grigaliunas et al, 2002;Toman et al, 2004).…”
Section: Cultured Drg Neurons Contain Slack K Na Channelssupporting
confidence: 87%
“…In neuronal simulations, K Na channels caused firing accommodation Brown et al, 2008). These findings are congruent with the fact that K Na channels are a prominent rectifying K ϩ current in neurons (Dale, 1993;Hess et al, 2007;Budelli et al, 2009;Lu et al, 2010). However, direct empirical evidence for K Na channel contribution to neuronal excitability has been lacking.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…It was shown in lamprey spinal cord neurons that AMPA receptor activation was linked, via Na ϩ transients, to an increase in K Na current amplitude (Nanou et al, 2008). Likewise, tetrodotoxin was shown to decrease strongly the outward K ϩ current evoked by depolarization in rat olfactory neurons, and a tetrodotoxin-sensitive K ϩ current was eliminated by a Slack small interfering RNA (Budelli et al, 2009). In locus ceruleus, glutamate-induced postactivation inhibition was found to be mediated by AMPA/kainate receptors and bithionol-sensitive K Na currents (Zamalloa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in the duration of AP following Tarragon oil treatment might be due to the inhibition of Na + and/or voltage-gated K + channels. It has now been reported that very small influxes of Na + through voltage-gated Na + channels activate a K + conductance which play an important role in determining AP duration in both vertebrate and invertebrate neurons (Bader et al,1985;Hartung, 1985;Dryer et al, 1989;Budelli et al, 2009). On the other hand, the results of the second sets of the experiments suggest that Tarragon extract has a potential antiepileptic effect.…”
Section: Discussionmentioning
confidence: 99%